The Effect of Ginger Decoction Intervention on Nausea and Vomiting in First Trimester Pregnancy: A Literature Review - Efendi, Melani Adelia; Bunga, Adelia; Ramadhani, Adinda Nasywa; Deviantony, Fitrio; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2025)
Introduction: During pregnancy, many mothers experience discomfort such as vomiting and nausea. During pregnancy, nausea and vomiting are common in Indonesia, with 50-75% of women experiencing symptoms in the first trimester or early pregnancy. Nausea and vomiting during pregnancy are caused by an increase in estrogen and human chorionic gonadotropin (HCG) hormone. Objective: To determine the effect of ginger decoction intervention on nausea and vomiting during pregnancy in the first trimester. Method: The method used is a literature review with a PRISMA protocol approach, with 6 journals found, 3 international, 3 nationals. The literature search process in this literature review uses 3 databases: PubMed, Google Scholar, and Science Direct, with a publishing period of 2019-2023. Results: Six research journals have shown that steeping ginger can reduce nausea and vomiting in pregnant women in the first trimester. Ginger has pharmacological effects as an antiemetic and can reduce the frequency of nausea and vomiting. The use of ginger can help pregnant women overcome the problem of nausea and vomiting during pregnancy. Conclusion: From the 6 studies obtained, it can be concluded that there is a significant effect of giving boiled ginger water as a nursing intervention in first-trimester pregnant women. As a complementary therapy, ginger water can effectively reduce the frequency of nausea and vomiting in pregnant women.